Rate, Predictors, and Consequences of Late Antenatal Booking in a National Cohort Study of Pregnant Women With HIV in Italy. Issue 3 (May 2014) - Floridia, M.; Pinnetti, C.; Ravizza, M.; Frisina, V.; Cetin, I.; Fiscon, M.; Sansone, M.; Antoni, A.Degli; Guaraldi, G.; Vimercati, A.; Guerra, B.; Placido, G.; et al.
Abstract : Objective: To evaluate the prevalence and consequences of late antenatal booking (13 or more weeks gestation) in a national observational study of pregnant women with HIV.Methods: The clinical and demographic characteristics associated with late booking were evaluated in univariate analyses using the Mann-Whitney U test for quantitative data and the chi-square test for categorical data. The associations that were found were re-evaluated in multivariable logistic regression models. Main outcomes were preterm delivery, low birthweight, nonelective cesarean section, birth defects, undetectable (<50 copies/mL) HIV plasma viral load at third trimester, delivery complications, and gender-adjusted and gestational age-adjusted Z scores for birthweight.Results: Rate of late booking among 1, 643 pregnancies was 32.9%. This condition was associated with younger age, African provenance, diagnosis of HIV during pregnancy, and less antiretroviral exposure. Undetectable HIV RNA at third trimester and preterm delivery were significantly more prevalent with earlier booking (67.1% vs 46.3%, P < .001, and 23.2% vs 17.6, P = .010, respectively), whereas complications of delivery were more common with late booking (8.2% vs 5.0%, P = .013). Multivariable analyses confirmed an independent role of late booking in predicting detectable HIV RNA at third trimester (adjusted odds ratio [AOR], 1.7; 95% CI, 1.3-2.3; P < .001) and delivery complications (AOR, 1.8; 95% CI, 1.2-2.8; P = .005).Conclusions: Late antenatal booking was associated with detectable HIV RNA in late pregnancy and with complications of delivery. Measures should be taken to ensure an earlier entry into antenatal care, particularly for African women, and to facilitate access to counselling and antenatal services. These measures can significantly improve pregnancy management and reduce morbidity and complications in pregnant women with HIV.